Analisis Anggaran Dan Realisasi Pendapatan dan Belanja Pada Rumah Sakit Umum Daerah Kramat Jati Tahun 2022 - 2023. - Fadillah Ashary,; Maria Sari Ayu,; Reza Agustur Karunia,; Suroso Suroso, (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study analyzes the budget and the realization of revenue and expenditure at Kramat Jati Regional General Hospital (RSUD) during 2022-2023. The aim is to evaluate revenue growth, expenditure, and the causes of discrepancies between the budget and realization. The findings indicate fluctuations in the growth ratio of revenue and expenditure. Discrepancies between the budget and realization are influenced by internal factors, such as operational management, and external factors, such as policy changes and economic conditions. This study provides recommendations for improving budget management efficiency at RSUD Kramat Jati.